Evaluation of Dietary Supplementation of Rosemary in Eastern Libya on Broiler's Performance, Carcass Traits and Some Blood Parameters. - Al-Mansory, A.R.; Gabriel , M.M; Sherif , .B.M (The Libyan Journal of Agriculture, 2023)
This study was conducted to evaluate the effect of dietary supplementation of rosemary (Rosmarinus officinalis) on the performance, carcass indices and some blood parameters of broilers. Ninety 14-day-old female broiler chicks (Ross 308) were used in this study. The chicks were allotted into 3 groups (30 chicks per group) and each group had 3 replicates (10 chicks per replicate). The control group was fed on a basal diet and the 2nd and 3rd treatments were fed on a basal diet supplemented with 0.4% and 0.5% of rosemary powder (RP) respectively. Diet and water are freely available for the duration of the trial, which lasted for 30 days. Our results indicated that rosemary supplementation significantly improved live body weight, body weight gain, feed intake, and feed conversion ratio. In addition to the improvement in the lipid profile, especially triglycerides and LDL, while it did not affect cholesterol and HDL, the results also showed an increase in globulin levels in the blood, while there was no negative effect on the carcass traits and the weight of the internal organs, as well as on the health status of the liver and kidneys. Collectively, rosemary supplementation is recommended at the level of 0.5% to the diet to improve the performance, physiological status and health status of broiler chicken.